IMMUNOLOGICAL FEATURES OF CHILDREN AT PRIMARY SCHOOL AGE WITH MYOPIA - Shmalyey, S.V.; Redka, I.V. (World of Medicine and Biology, 2012)
In the article the state of lymphocytic, humoral and phagocytic the immune system of children of primary school age with the stable myopia are analyzed. It is established that children from stable miopiy different degree are characterized by the expressed immunoscarce condition which is caused by violation of process of a proliferation of T-lymphocytes and the raised level of negative activation of T-lymphocytes (apoptosis); violation of cooperation of T- and B-lymphocytes; hypoimmunoglobulenemia A and M; the reduced phagocytical activity of neutrophils. Defined immunological criteria transition emetropic refraction in different variants of myopic refraction.